Satellite Communication Synchronization Based on Combining Multi-Differential Correlations in the High Doppler Channel - Liu, Jiancheng; Wang, Saiyu; Hao, Zhisong; Zhang, Jingtao (Společnost pro radioelektronické inženýrství, 2021)
In this paper, a pilot-aided synchronization method based on combining multi-differential correlations (MDCS) is proposed to overcome the obstacles in the synchronization of high-speed mobile satellite communication links. The proposed approach can optimally use the original synchronization pilot, and the existing transmitter would not need any modification. Additionally, the performance of proposed method is investigated on theoretical level, including the principle of mitigating the frequency offset deterioration and the derivation of closed synchronization probability expression. Finally, a set of simulations were operated to verify the MDCS performance, and the results proved that the MDCS significantly outperformed the existing approaches for large frequency offset and strong channel noise.
Keywords: Satellite communication; pilot-aided synchronization; multi-differential correlation; high Doppler channel; frequency offset